2021
DOI: 10.1111/1475-6773.13706
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adoption of robotic radical prostatectomy in the United States and England

Abstract: Objectives: To compare patterns of technological adoption of minimally invasive surgery for radical prostatectomy across the United States and England. Data Sources: We examine radical prostatectomy in the United States and England between 2005 and 2017, using de-identified administrative claims data from the OptumLabs Data Warehouse in the United States and the Hospital Episodes Statistics in England. Study Design: We conducted a longitudinal analysis of robotic, laparoscopic, and open surgery for radical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…We further found that 5,501 (22.8%) and 4,338 (22.1%) prostatectomies were performed without the robotic systems in 2019 and 2020, respectively. More than 500 robotic systems have been introduced in Japanese hospitals, and the prevalence of RARP is almost equivalent to that in the United States and England (5).…”
mentioning
confidence: 99%
“…We further found that 5,501 (22.8%) and 4,338 (22.1%) prostatectomies were performed without the robotic systems in 2019 and 2020, respectively. More than 500 robotic systems have been introduced in Japanese hospitals, and the prevalence of RARP is almost equivalent to that in the United States and England (5).…”
mentioning
confidence: 99%
“…As previously described, there has been substantial growth in robotic procedures throughout the world. In a review of data from the OptumLabs Data Warehouse in the United States and the Hospital Episodes Statistics in England, investigators demonstrated that robotic surgery has become the standard approach for radical prostatectomy in the United States and England [ 13 ]. Similarly, utilization of robotic proctectomy for rectal cancer has also steadily increased [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, reductions in LOS for robotic procedures have not been consistently reported in prior analyses. For example, in an analysis of patients with rectal cancer investigators reviewed claims data from 2005 through 2017, reporting decreased LOS for robotic surgery as compared to open surgery [ 13 ]. In contrast, although the lung cancer literature reveals reductions in hospital LOS for minimally invasive approaches as compared to open lung surgery [ 8 ], analyses of robotic lung surgery have not demonstrated appreciable gains in LOS as compared to VATS [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robot‐assisted radical prostatectomy (RARP) for prostate cancer is now well‐established in settings where robotic surgical systems are available. The number of RARP per year overtook open radical prostatectomy (ORP) in 2009 in the United States of America (U.S.A), 1 in 2012 in England, 2 and in 2015 in Australia 3 . The proportion of RARP increased to 85% in the United States in 2013, 1 93% in England in 2018, 2 and 65% in Australia in 2019 3 .…”
Section: Figmentioning
confidence: 99%